Differences Between Groups of Pre-exposure Prophylaxis (PrEP) Using Couples in HIV-Negative/Unknown Relationships. (1st August 2019) - John, Steven A.; Robles, Gabriel; Starks, Tyrel J.; Rendina, H. Jonathon
Abstract : Background: Epidemiology research is limited on the characteristics of HIV pre-exposure prophylaxis (PrEP) using couples. Setting: US nationwide sample recruited online in 2017. Methods: HIV negative/unknown gay, bisexual, and other men who have sex with men with HIV negative/unknown partners (n = 3140) were asked about individual and main partner PrEP uptake. Men were coded into the following 5 groups: (1) neither participant nor partner on PrEP, (2) partner only on PrEP, (3) participant only on PrEP, (4) both on PrEP, and (5) unknown partner PrEP use. We examined associations of demographics, relationship factors, condomless anal sex (CAS) with main and causal partners, bacterial sexually transmitted infection diagnoses, and sexual positioning with reported dyadic PrEP use using fully adjusted multinomial logistic regressions. Results: PrEP use was 3.2% for the partner only, 5.7% for the participant only, and 4.9% for both the participant and partner; 5.6% reported not knowing their partner's PrEP use status. Men who reported any CAS with their main partner or any CAS with male casual partners were both more likely to be classified in the dyadic PrEP use group compared with the neither on PrEP group. Compared with monogamous, men in open arrangements were more likely to be classified in each of the 3 PrEP groups compared with the neither on PrEP group. Six-month bacterial sexually transmitted infection prevalence was 2.8%, 8.1%, 8.3%, 15.6%, and 4.0% for the 5 groups, respectively. Conclusions: PrEP use occurred during times of higher risk behavior engagement, but further efforts are needed to expand PrEP use to more partnered gay, bisexual, and other men who have sex with men.